Black Blood MRI in Suspected Large Artery Primary Angiitis of the Central Nervous System. Issue 3 (28th August 2012) - Pfefferkorn, Thomas; Linn, Jennifer; Habs, Maximilian; Opherk, Christina; Cyran, Clemens; Ottomeyer, Caroline; Straube, Andreas; Dichgans, Martin; Nikolaou, Konstantin; Saam, Tobias
Abstract : ABSTRACT: OBJECTIVES: Single case reports suggest that black blood MRI (T1‐weighted fat and blood suppressed sequences with and without contrast injection; BB‐MRI) may visualize intracranial vessel wall contrast enhancement (CE) in primary angiitis of the central nervous system (PACNS). In this single‐center observational pilot study we prospectively investigated the value of BB‐MRI in the diagnosis of large artery PACNS. METHODS: Patients with suspected large artery PACNS received a standardized diagnostic program including BB‐MRI. Vessel wall CE was graded (grade 0‐2) by two experienced readers blinded to clinical data and correlated to the final diagnosis. RESULTS: Four of 12 included patients received a final diagnosis of PACNS. All of them showed moderate (grade 1) to strong (grade 2) vessel wall CE at the sites of stenosis. A moderate (grade 1) vessel wall CE grade was also observed in 6 of the remaining 8 patients in whom alternative diagnoses were made: arteriosclerotic disease ( n = 4), intracranial dissection ( n = 1), and Moyamoya disease ( n = 1). CONCLUSIONS: Our pilot study demonstrates that vessel wall CE is a frequent finding in PACNS and its mimics. Larger trials will be necessary to evaluate the utility of BB‐MRI in the diagnostic workup of PACNS.